ALLAH, ALAM, DAN POTENSI MANUSIA - Nanang Qosim (UNZAH Genggong, 2020)
Humans as the main actors on earth are equipped with a variety of potential that is not possessed by other creatures. This potential aside from being a medium to fulfill his duties as a caliph is also evidence of the manifestation of God. This paper examines the potential of humans as representatives of God on earth and their interactions with nature and God. Keyword: Human, Potential, Allah